Sentimen Analisis Overclaim Skincare Skintific Menggunakan Algoritma BERT - Hingis, Kharlina; Karolina , Umi; Pribadi , Risky (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This year, the use of Skintific skincare products has experienced a significant surge in sales percentages. Based on observations in the beauty and cosmetics market, Skintific has recorded revenues reaching billions to trillions of rupiahs annually. This indicates that business opportunities in the beauty industry are highly promising, especially in recent years. However, intense competition in the beauty industry has given rise to numerous new cosmetic brands that often promote their products excessively, a practice known as overclaim. This behavior is often carried out unconsciously, yet it misleads targeted consumers and constitutes fraudulent practices. In this study, the author conducted a scraping process of customer reviews on Skintific cosmetics from Instagram, one of the popular social media platforms. The approach used was a Deep Learning method with the BERT (Bidirectional Encoder Representations from Transformers) algorithm. The research analyzed 1,000 customer reviews from the official Instagram account of Skintific. The findings reveal that the phenomenon of overclaim in Skintific products was only 0.0015% of the total reviews, which is starkly lower compared to other cosmetic products in the beauty industry